Yesterday’s watercraft, tomorrow’s watercraft. Documenting the 20th century wooden watercraft abandoned on the banks of Basque intertidal estuaries - Matés Luque, José Manuel (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
In the Basque Country there are many wooden watercraft abandoned on the banks of estuaries. They are a rich source of information for insight into not only ships and boats built in the 20th century, of which the last examples have been disappearing since the 1980s, but also they may provide information on older watercraft as they represent the last stage in ship- and boat-building rooted in the Middle Ages. Study of these watercraft has revealed interesting details that engender an understanding of the possible evolution of medieval and/or 16th century features. Hence the need to document such contemporary and abandoned watercraft is vital.